Reform and Reformulation of Public Policy in Indonesia: What is required? - Widhiasthini, Ni Wayan; Utami, Made Srinitha Millinia; Subawa, Nyoman Sri (Journal of Government and Civil Society, 2024)
Public policy reform in Indonesia has emerged as a critical area of study over the past few decades, necessitating a comprehensive examination of its underlying instruments and models. This research aims to identify essential components and develop strategic frameworks for the effective reform and reformulation of public policy within the Indonesian government. Through an extensive thematic analysis of previous policy reforms, this study highlights recurring themes and successful patterns that inform best practices. Findings underscore the urgent need for reforms in the public service and agribusiness sectors, as well as the broader governance framework, to enhance policy effectiveness and societal outcomes. While political stability remains a vital prerequisite for successful public policy implementation, it is insufficient in isolation. The integration of Multi-Level Governance (MLG), active stakeholder engagement in policy development, and the incorporation of technological advancements are pivotal for facilitating meaningful reforms. Furthermore, political and governance reforms are essential to address emerging challenges. The adoption of data and system analytics within government agencies has shown promise in enhancing policy initiatives; however, it raises critical concerns about privacy and accountability. In the context of Indonesia's dynamic and diverse landscape, this research advocates for a strategic dissemination of substantial data to various stakeholders to foster informed decision-making and effective public policy reform. Reformasi kebijakan publik di Indonesia telah muncul sebagai area studi yang kritis selama beberapa dekade terakhir, yang memerlukan pemeriksaan menyeluruh terhadap instrumen dan model yang mendasarinya. Penelitian ini bertujuan untuk mengidentifikasi komponen penting dan mengembangkan kerangka strategis untuk reformasi dan reformulasi kebijakan publik yang efektif dalam pemerintahan Indonesia. Melalui analisis tematik yang komprehensif terhadap reformasi kebijakan sebelumnya, penelitian ini menyoroti tema-tema yang berulang dan pola sukses yang dapat menginformasikan praktik terbaik. Temuan menunjukkan kebutuhan mendesak akan reformasi di sektor pelayanan publik dan agribisnis, serta kerangka tata kelola yang lebih luas, untuk meningkatkan efektivitas kebijakan dan hasil sosial. Meskipun stabilitas politik tetap menjadi prasyarat vital untuk pelaksanaan kebijakan publik yang sukses, hal ini tidak cukup jika berdiri sendiri. Integrasi Multi Level Governance (MLG), keterlibatan aktif pemangku kepentingan dalam pengembangan kebijakan, dan penggabungan kemajuan teknologi merupakan hal yang penting untuk memfasilitasi reformasi yang bermakna. Selain itu, reformasi politik dan tata kelola diperlukan untuk mengatasi tantangan yang muncul. Adopsi data dan analitik sistem dalam lembaga pemerintah menunjukkan janji dalam meningkatkan inisiatif kebijakan; namun, ini menimbulkan kekhawatiran kritis mengenai privasi dan akuntabilitas. Dalam konteks lanskap Indonesia yang dinamis dan beragam, penelitian ini menganjurkan untuk penyebaran data substansial secara strategis kepada berbagai pemangku kepentingan guna mendorong pengambilan keputusan yang terinformasi dan reformasi kebijakan publik yang efektif.